Revitalizing the Mosque’s Role as an Economic Stabilizer for the Muslim Community: Social Fiqh Perspectives and Contemporary Practice - Mowafg Masuwd (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Since the time of the Messenger of Allah ﷺ, the mosque has functioned not only as a center of worship but also as a social institution with a strategic role in developing the community’s economy. However, over time its function has tended to be reduced to ritual religiosity alone, leaving its role as a stabilizer of the community’s economy less than optimal. This article aims to reassess the mosque’s functions through the lens of social fiqh and their implementation in contemporary practice. The approach employed is normative-empirical: it examines Qur’anic verses, hadiths, and classical fiqh literature, then contextualizes them within modern mosque management practices encompassing the administration of zakat, infaq, charity (sadaqah), and productive waqf. The findings indicate that revitalizing the mosque’s functions can serve as an instrument for wealth distribution, the economic empowerment of congregants, and the safeguarding of Islamic business ethics. In addition, contemporary practice reveals models of “productive mosques” capable of becoming centers for community-based economic empowerment. Thus, the mosque holds significant potential as a pillar of the socio-economic balance of Muslim society, provided it is managed professionally, accountably, and in integration with Islamic financial institutions.